Bottom-Up (Cu, Ag, Au)/Al2O3/Bi2Te3 Assembled Thermoelectric Heterostructures - Zhenhua Wu; Shuai Zhang; Zekun Liu; Cheng Lu; Zhiyu Hu (Micromachines, 2021)
The interface affects the transmission behavior of electrons and phonons, which in turn determines the performance of thermoelectric materials. In this paper, metals (Cu, Ag, Au)/Al2O3/Bi2Te3 heterostructures have been fabricated from bottom to up to optimize the thermoelectric power factor. The introducing metals can be alloyed with Bi2Te3 or form interstitials or dopants to adjust the carrier concentration and mobility. In addition, the metal-semiconductor interface as well as the metal-insulator-semiconductor interface constructed by the introduced metal and Al2O3 would further participate in the regulation of the carrier transport process. By adjusting the metal and oxide layer, it is possible to realize the simultaneous optimization of electric conductivity and Seebeck coefficient. This work will enable the optimal and novel design of heterostructures for thermoelectric materials with further improved performance.